Peranan Administrasi Pendidikan dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Islam (PAI) pada MTs DDI Cilellang Kabupaten Barru - Salmiati Salmiati; Riyang Septiawansyah (Madrasah Tsanawiyah DDI Cilellang, 2019)
This research discusses the role of educational administration, in this case, the learning device as an effort to increase Islamic education teacher professionalism at MTs DDI Cilellang, Barru Regency. The aims are to analyze: 1) the state of educational administration made by the teacher; 2) the form of teacher professionalism; and 3) the contribution of educational administration in increasing teacher professionalism. The type of this research is qualitative with descriptive method. Informants in this research were teachers of Al-Qur'an-Hadis, teachers of Akidah Akhlak, teachers of Fikih, and teachers of Islamic Culture History (SKI) at MTs DDI Cilellang, Barru Regency. The results showed that the state of teacher education administration at MTs DDI Cilellang, Barru Regency was complete and was well applied in the learning process in the classroom. The form of teacher professionalism is carrying out duties, roles, and responsibilities as teachers well. The contributions of educational administration in developing teacher professionalism at MTs DDI Cilellang, Barru Regency are five, namely: (1) time management, (2) class management, (3) stimulating to innovate, (4) stimulating to develop technical skills, (5) and the concept of transformation of students.